Characterization of electrothermal micro-actuator using image processing algorithm - AKKUŞ, NİHAT (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2021)
3D fabrication technology has gained a lot of attention recently, with the rapid fabrication of 3D parts for use in various applications. This article presents an electrothermal micro-actuator's characterization study fabricated using digital light processing (DLP), one of the 3D manufacturing methods. This actuator has been designed and fabricated to move in two directions according to the specified criteria. Three different experiments were conducted during the fabrication process. During the fabrication process of the first two experiments, deterioration or breakage occurred in the micro-actuator structure. These problems did not occur in the fabrication of the 3rd experiment. A characterization test setup was created to observe the displacement of the actuator under different operating voltage values. This setup includes an optical microscope and digital camera to observe displacements at the probe station. An image processing algorithm was used to detect the observed displacements. In experimental studies, the operating voltage was increased from 0V to 1V until deterioration or breakage in the micro-actuator structure was observed. When 6V voltage is applied to the micro-actuator, a maximum displacement of 3.84 mu m occurred in each direction. When more than 6V voltage is applied to the micro-actuator, deformations or breaks occurred in the actuator arms. As a result, the micro-actuator's design is bi-directional, so its maximum displacement is 7.68 mu m.
Keywords: Digital light processing; 3D fabrication; Electrothermal microactuator; Characterization; Image processing; DESIGN; MICROGRIPPER